Local partnerships and urban governance: The case of Lisbon - Pappa, A.; Paio, A. (Conference Housing co-creation for tomorrow’s cities Co-création de l’habitat pour les villes de demain, 2022)
Collaborative forms of governance in urban regeneration are increasingly gaining ground in cities around the world, contributing to the active engagement of citizens in decision-making processes that affect their neighbourhoods and lives. In some cases, municipalities embrace local grassroot initiatives, as for example with the implementation of participatory budgets, enabling active citizens to creatively invent ways to regain and co-manage the urban commons. In a similar vision, the Department of Housing and Local Development of the Municipality of Lisbon launched in 2011 a participatory budget program, namely BIP/ZIP, to annually fund bottom-up initiatives led by local partnerships in priority neighbourhoods that enable responses to social and territorial emergencies. The aim of this research is to investigate the matrix of local partnerships that have been formulated throughout the eleven years of BIP/ZIP and understand their dynamic role in the transformation of the urban governance in the city of Lisbon.